Enhancing Organic Contaminant Removal from Wool Scouring Wastewater Using Chemically Modified Biochars - Simeng Li; Desarae Tasnady; Shannon Skelley; Blanca Calderon; Sherine Jiang (C, 2024)
In recent times, biochar has emerged as a promising and sustainable solution for COD reduction in wastewater treatment. This study explores the potential of chemically modified biochars as efficient adsorbents for the removal of organic contaminants, specifically oils, fats, and grease (OFG), from wool scouring wastewater. Proximate analysis revealed distinct properties among the biochars, with KOH-treated biochar demonstrating the most promising characteristics, including lower volatile matter, higher fixed carbon content, and reduced ash content, indicating a stable and carbon-rich structure. A meticulous examination of the KOH-treated biochar’s surface characteristics revealed the presence of elevated carbon and nitrogen content, complemented by an expansive surface area measuring 724.4 m2/g. This surface area was at least twice as extensive as that observed in the other post-treated biochar samples. The kinetic adsorption of COD and soluble COD was well fitted by the pseudo-first-order model, with equilibrium achieved in approximately 200 min. The KOH-treated biochar exhibited the highest equilibrium adsorption capacities for both COD and soluble COD in both Dorset wool (Dorset) and Bluefaced Leicester (BFL) wastewater, highlighting its efficacy in OFG removal. Despite these promising results, further research is needed to explore biochar’s surface characteristics, pore structure, and performance under diverse conditions, as well as its integration with existing treatment processes and potential for regeneration and reuse. This study contributes to advancing sustainable wastewater treatment methods using chemically modified biochars.